Arcanobacterium ihumii sp. nov., Varibaculum vaginae sp. nov. and Tessaracoccus timonensis sp. nov., isolated from vaginal swabs from healthy Senegalese women. (September 2019) - Fall, N.S.; Lo, C.I.; Fournier, P.-E.; Sokhna, C.; Raoult, D.; Fenollar, F.; Lagier, J.-C.
Abstract: Culturomics studies the microbial variety of the human microbiome by combining diversified culture conditions, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and 16S rRNA gene identification. This study identifies three putative new bacterial species: Arcanobacterium ihumii sp. nov. strain Marseille-P5647 T, Varibaculum vaginae sp. nov. strain Marseille-P5644 T and Tessaracoccus timonensis sp. nov. strain Marseille-P5995 T, which we describe according to the concept of taxonogenomics.